(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
This first volume of the review "L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni“ a double monographic issue produced in 2013 develops the theme of "Ludovico Quaroni the Architect”. This is undoubtedly a direct result of the pleasure of beginning the publication by paying homage to the master in whose name we have undertaken this project. However, it is above all our intention to once again focus attention on the fundamental aspects of Ludovico Quaroni’s ideas on architecture, and its relationships with the city, through a unique critical analysis of archival material, original drawings and new testimonials. This is why we have chosen to examine a range of very different projects, various scales and different themes requiring diverse commitments. We will examine both built and unbuilt works, not always familiar or in any case not fully known, despite the fact that many were at the centre of modern architectural debate in post-war Italy. As always, for the same reasons underlying our own project, we believe it important to offer non-Italian scholars the opportunity to participate in this collective reflection and to evaluate its meaning; for this reason the articles published in the review have been rendered accessible to a vaster public through their integral translation in English. The review investigates projects from a period in history that covers almost the entire period of Ludovico Quaroni’s professional career; we have selected at least one project per decade, spanning from the 1940s to the 1980s. As demonstrated by the table of contents, the essays are published in the same chronological order as the original projects.